Digital Turn und Historische Bildungsforschung Bestandsaufnahme und Forschungsperspektiven - Oberdorf, Andreas (Verlag Julius Klinkhardt, 2022)
In recent decades, historical educational research has developed into a field of research and work that is multifaceted in its topics, methods, and theoretical references and is interdisciplinary. The methods, working techniques, and tools of the digital humanities, which influence many areas of the humanities and cultural studies today, are also already being applied there in a variety of ways. This volume demonstrates this with concrete examples from current research projects and working groups related to historical education research. The contributions give examples of the application of selected digital tools and research methods and put research-practical as well as epistemological questions up for discussion.